The Effect of Flexible Working Perception, Digital and Agile Organizational Culture on Technology Use: a Study from the Employees’ Perspective - Ömür Gökçe Akdemir; Öztirak Mesut; Yazici Ayşe Meriç; Çiçeklioğlu Hüseyin (Studia Humana)
The purpose of this study is to examine the interaction of flexible working perception with digital and agile organizational cultures and the effects of this interaction on technology use from the perspective of employees. The research was carried out with data collected from 382 employees operating in different sectors (technology, finance, education, health) on the European Side of Istanbul. The data were collected using structured questionnaires and confirmatory factor analysis (CFA), item-total correlation, Cronbach Alpha methods, correlation analysis and path analysis method were used within the scope of validity and reliability studies of the scales. In the study, a positive and significant relationship was found between the variables of flexible working and digital and agile organizational culture and technology use, while the perception of flexible working had a positive and significant effect on the perception of technology use. The study also concluded that digital and agile organizational culture has a significant effect on the perception of technology use. According to the results of the study, the perception of flexible working and digital and agile organizational cultures have a positive and significant effect on employees’ use of technology.